Preparation and Mounting of Whole Blood Clot Samples for Mechanical Testing. Issue 7 (19th July 2021) - Sugerman, Gabriella P.; Chokshi, Armaan; Rausch, Manuel K.
Abstract: Studying and quantifying the mechanics of blood clots is essential to better diagnosis and prognosis of, as well as therapy for, thromboembolic pathologies such as strokes, heart attacks, and pulmonary embolisms. Unfortunately, mechanically testing blood clots is complicated by their softness and fragility, thus making the use of classic mounting techniques, such as clamping, challenging. This is particularly true for mechanical testing under large deformation. Here, we describe protocols for creating in vitro blood clots and securely mounting these samples on mechanical test equipment. To this end, we line 3D‐printed molds with a hook‐and‐loop fabric that, after coagulation, provides a secure interface between the sample and device mount. In summary, our molding and mounting protocols are ideal for performing large‐deformation mechanical testing, with samples that can withstand substantial deformation without delaminating from the apparatus. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Cube‐shaped blood clot preparation Basic Protocol 2 : Sheet‐shaped blood clot preparation